Microbiological Examination of Escherichia coli and Salmonella on Fishery Products at Fish Quarantine Station, Quality Control and Safety of Fishery Products Yogyakarta - Mohammad Faizal Ulkhaq, S.Pi., M.Si; I.A.; H. Kenconojati; I.N. Putriantini; Inaiyah Inaiyah (Airlangga University, 2021)
Microorganisms that often contaminate fishery products were from bacteria groups. Some spesies of bacteria were harmful to human health because they can cause disease and even death in humans, such as Escherichia coli and Salmonella. Therefore its were needed for quarantine and microbiological examination of fishery products as an effort to prevent the spread of disease in humans. The aims of this study were to identify the contamination of E. coli and Salmonella bacteria in fishery products. A total eight samples of fishery products tested consist of canned dan frozen products using conventional methods based on ISO 16649-3: 2015 for E. coli and ISO 01-2332.2-2006 for Salmonella. The results showed that one from the six fishery products tested were frozen boiled tuna that positively E. coli and no fishery product sample was identified with Salmonella.